2016
DOI: 10.18702/acf.2016.06.2.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and fatigue behavior of prestressed concrete beams made with portland pozzolana cement

Abstract: There is rapid growth of Portland Pozzolana Cement (PPC) production over the last few years. The use of PPC has been included by Indian and international standards/specifications in the past. But in India, the use of PPC for prestressed concrete (PSC) is generally not recommended in different specifications due to apprehension of late strength development and a lack of data on other critical properties of PSC like creep, shrinkage, and fatigue. The critical properties affecting PSC structures such as strength,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Admixtures like retarders can be added to increase the setting time of RCC. Fine aggregates in RCC are more than compared to standard concrete which can be seen as a difference between RCC and standard concrete [11]. More fine aggregates offer better packing and consolidation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Admixtures like retarders can be added to increase the setting time of RCC. Fine aggregates in RCC are more than compared to standard concrete which can be seen as a difference between RCC and standard concrete [11]. More fine aggregates offer better packing and consolidation [12].…”
Section: Introductionmentioning
confidence: 99%
“…200 sieve is particularly greater for RCC than for conventional concrete and details for this are not laid down in IS: 383-2016 [33]. The larger percentage of fines is needed to fill voids in cement paste that would otherwise be filled with cementitious materials in case of conventional concrete [44][45]. Addition of fines are usually made up of naturally occurring non-plastic silt and fine sand or manufactured fines.…”
Section: Concrete MIX Compositionmentioning
confidence: 99%
“…This increase in flexural and split tensile strength of high strength conventional Portland cement concrete is similar to findings of Arora et.al [16,40,41] wherein it was reported that flexural strength of silica fume concrete was higher by 10-15% as compared that of Portland cement concrete for about 12-15 % silica fume addition. The addition of silica fume in concrete mix leads to reduction in the development of cracks at micro level near the interface of cement paste and unreacted cement or pozzolans [30,42,43,44,45]. Modulus of elasticity of M40RGC is about 70.00 % of modulus of elasticity of M40RCC and Modulus of elasticity of M70RGC is about 77 % of Modulus of elasticity of M70RCC.…”
Section: Mechanical Properties Of Mixesmentioning
confidence: 99%